2014
DOI: 10.1007/s12010-014-1044-6
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Chymosin from Rhizopus microsporus var. rhizopodiformis

Abstract: Purification and characterization of a chymosin from Rhizopus microsporus var. rhizopodiformis were investigated in the present study. A newly isolated R. microsporus var. rhizopodiformis F518 produced a high level of milk-clotting activity (1,001 SU/mL). A chymosin from the fungus was purified 3.66-fold with a recovery yield of 33.2 %. The enzyme appeared as a single protein band on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) with a molecular mass of 37.0 kDa. It was optimally active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
2
13
0
1
Order By: Relevance
“…However, at 50–60C, they retained only 10–20% of its activity after 30 min (Rao and Mathur 1979; Sun et al . ). No changes were observed in the protease activity of Rhizomucor miehei between 55 and 62C, where it retained ∼80% activity.…”
Section: Resultsmentioning
confidence: 97%
“…However, at 50–60C, they retained only 10–20% of its activity after 30 min (Rao and Mathur 1979; Sun et al . ). No changes were observed in the protease activity of Rhizomucor miehei between 55 and 62C, where it retained ∼80% activity.…”
Section: Resultsmentioning
confidence: 97%
“…1E), and it decreased at higher speeds due to increased mechanical shear force that was not conducive to cell growth (Hashem, 2000;Narwal et al, 2017). Proper agitation of culture would facilitate MCA by letting in more air, therefore oxygen, but some other studies presented otherwise different results, that still culture would yield a higher MCA (Hashem, 2000;Narwal et al, 2017;Sun et al, 2014), which was possible due to the differences in the nature of strains. He et al (2012) indicated that the initial pH of growth medium strongly affected enzyme reaction and transport of various components across the cell membrane, thus the MCA of B. methanolicus LB-1.…”
Section: Resultsmentioning
confidence: 97%
“…Milk-clotting enzymes from other fungi as Rhizopus oryzae (Kumar et al, 2005), Penicillium oxalicum (Hashem, 1999) and Rhizopus microsporus var. rhizopodiformis (Sun et al, 2014) also presented optimum activity at 60°C. According to Dybowska and Fujio (1996) at high values of temperature, the process of coagulation is decreased.…”
Section: Al (2015)mentioning
confidence: 94%
“…Sun et al (2014) showed that Zn 2+ ions raised the milk-clotting enzyme activity from R. microsporus var. rhizopodiformis.…”
Section: Al (2015)mentioning
confidence: 99%